The Influence of Employee Quality of Work Life and Training on Employee Performance through Work Motivation at Hotel Grand Whiz Trawas - Iffat, Emmira; Sriyono; Sukmono, Rita Ambarwati (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2024)
The tourism industry in Indonesia is experiencing slow growth due to the impact of the global economic crisis. The Grand Whiz Trawas Hotel faces suboptimal employee performance and fluctuating employee turnover rates, suspected to be influenced by factors such as quality of work life, training, and employee motivation. This research aims to analyze the influence of Employee Quality of Work Life and Training on Employee Performance through Employee Motivation at the Grand Whiz Trawas Hotel. The research employs quantitative techniques with a hypothesis-testing research design. The population consists of all employees at the Grand Whiz Trawas Hotel, totalling 93 individuals, with sample determination using a saturated sampling technique where all population members are used as samples. Data collection is conducted using a Likert scale. The research will be analyzed using Partial Least Squares (PLS) and a purposive sampling approach. Results managerial implications show that quality of life, training, and work motivation significantly influence employee performance. Work motivation also acts as a mediating variable in the model. These findings prove that improving employee performance at the Grand Whiz Trawas Hotel enhances quality of life, training, and work motivation. Academically, this model can serve as a reference for further research by adding other variables such as organizational development and talent management. Managerial implications include skills matching, re-vising policies on work cycles and promotions, evaluating compensation, promoting mentorship programs, ensuring flexible schedules for working mothers, and addressing global skills mismatches and gaps